2021
DOI: 10.1371/journal.pone.0254591
|View full text |Cite
|
Sign up to set email alerts
|

Team numerical advantage in Australian rules football: A missing piece of the scoring puzzle?

Abstract: The primary aim of this study was to determine the relationship between a team numerical advantage during structured phases of play and match event outcomes in professional Australian football. The secondary aim was to quantify how players occupy different sub-areas of the playing field in match play, while accounting for match phase and ball location. Spatiotemporal player tracking data and play-by-play event data from professional players and teams were collected from the 2019 Australian Football League seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…centre bounces, ball ups and throw ins) where there is a higher density of players around the ball. 27 These findings correspond to previous research which reported increased tackles in smaller sized SSG compared to larger sized SSG. 16 Indeed, the spatial movements of players are more unpredictable when player numbers are lower, 28 suggesting the larger spaces with a lower number of players and increased unpredictability of movements may make it more difficult for players to make tackles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…centre bounces, ball ups and throw ins) where there is a higher density of players around the ball. 27 These findings correspond to previous research which reported increased tackles in smaller sized SSG compared to larger sized SSG. 16 Indeed, the spatial movements of players are more unpredictable when player numbers are lower, 28 suggesting the larger spaces with a lower number of players and increased unpredictability of movements may make it more difficult for players to make tackles.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, numerical advantages during structured phases of play has shown a greater likelihood of gaining possession from clearances or generating scores in professional AFL matches. 27 Consequently, coaches may constrain the environment with an outnumber to the attacking team to probe and encourage degenerate behaviour during practice and further emphasise features in the environment which invite the players to behave functionally. 27,30 Whilst this may be valuable for training particular behaviours, coaches need to remain mindful that generating an outnumber in play should be valued more so than purely ‘allocating’ or prescribing an outnumber during practice.…”
Section: Discussionmentioning
confidence: 99%
“…After a team obtains possession of the ball in the defensive half, the opposition may fold back in numbers to establish defensive stability, rather than press up the field to instigate a turnover in possession. Corresponding studies corroborate this tactical team behaviour in AF, whereby teams produced a numerical advantage in their defensive half [35]. Although disposals in low congestion decreased in the F50 compared to the AM, this is likely due to set shots on goal.…”
Section: Plos Onesupporting
confidence: 62%
“…However, scoring rates have remained stubbornly subdued [ 36 ], which suggests that the current rule changes may not be enticing teams to alter their collective movement behaviour. Indeed, previous studies support this sentiment in AF, whereby teams are preserving a numerical advantage in their defensive 50, which reduces the likelihood of generating a shot on goal [ 35 ]. The direct causes of reduced scoring rates are likely multifaceted and require further investigation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation